2019
DOI: 10.1002/pd.5544
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women with confirmed neoplasms should not have noninvasive prenatal testing

Abstract: What's already known about this topic? Incidental diagnoses of an occult maternal malignancy have been reported upon aberrant routine noninvasive prenatal testing (NIPT).The presence of tumor‐derived cell‐free DNA in the maternal circulation can skew the NIPT profile. What does this study add? Pregnant women with a confirmed neoplastic disease should not have NIPT testing for fetal aneuploidy screening since NIPT results cannot accurately be applied to assess the fetal chromosomal constitution in this conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Because fetal cfDNA fractions exist in a high background of maternal cfDNA, NIPT can also detect maternal chromosomal abnormalities, like those resulting from maternal mosaicisms or malignancies [3] . Indeed, various reports have shown that NIPT detection of tumor-derived cfDNA (ctDNA) in pregnant women with an occult malignancy was causing the aberrant cfDNA signal thereby disturbing the interpretation of fetal trisomies [4] , [5] , [6] , [7] , [8] , [9] . As the use of NIPT is increasingly expanding to low-risk pregnancies - in some countries it is offered as a first-tier test to all pregnant women - and its scope is being broadened beyond aneuploidy screening, more aberrant results, caused by a malignancy, are expected to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Because fetal cfDNA fractions exist in a high background of maternal cfDNA, NIPT can also detect maternal chromosomal abnormalities, like those resulting from maternal mosaicisms or malignancies [3] . Indeed, various reports have shown that NIPT detection of tumor-derived cfDNA (ctDNA) in pregnant women with an occult malignancy was causing the aberrant cfDNA signal thereby disturbing the interpretation of fetal trisomies [4] , [5] , [6] , [7] , [8] , [9] . As the use of NIPT is increasingly expanding to low-risk pregnancies - in some countries it is offered as a first-tier test to all pregnant women - and its scope is being broadened beyond aneuploidy screening, more aberrant results, caused by a malignancy, are expected to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…37 As a consequence, non-invasive prenatal testing in women with a known cancer diagnosis is non-informative and alternative prenatal screening testing should be offered. 38 Obstetric Ultrasound Available large case series reveal that neonates prenatally exposed to chemotherapy are at risk of being born small for gestational age, defined as a customized birth weight percentile below 10. 5 Besides constitutionally small neonates, explained by inherited factors, this definition also incorporates fetuses that did not reach their growth potential and are pathologically growth-restricted.…”
Section: Obstetric Managementmentioning
confidence: 99%
“…37 As a consequence, non-invasive prenatal testing in women with a known cancer diagnosis is non-informative and alternative prenatal screening testing should be offered. 38 …”
Section: Obstetric and Perinatal Managementmentioning
confidence: 99%
“…Indeed, cancer can be identified accidentally after an aberrant noninvasive prenatal testing result, not unusually observed as a simultaneous presence of imbalances in several chromosomes. 2 This not only will result in an inconclusive noninvasive prenatal testing result, but also should raise awareness of potential underlying maternal cancer. Diffusion-weighted whole-body magnetic resonance imaging is used in our clinic to examine these women for an underlying malignancy.…”
mentioning
confidence: 99%
“…Furthermore, noninvasive prenatal testing in women with earlier diagnosed cancer is noninformative because cancer potentially skews the test results. 2 These women should be advised of alternative screening or testing options, including nuchal thickness measurement and a structural ultrasonography.…”
mentioning
confidence: 99%